2004
DOI: 10.1017/s0025315404010392h
|View full text |Cite
|
Sign up to set email alerts
|

First records of the oriental prawn Palaemon macrodactylus (Decapoda: Caridea), an alien species in European waters, with a revised key to British Palaemonidae

Abstract: This paper details the ¢rst recorded instance of the prawn Palaemon macrodactylus in Europe, at the Orwell estuary, Su¡olk. The species is native to north-east Asia, including Japan and Korea, and has previously been introduced to other areas outside its natural range. Records of the abundance of caridean species, obtained from routine benthic trawl samples in the Stour and Orwell estuaries, provide a summary of P. macrodactylus' habitat preference in reduced-salinity waters. Consistent catches and records of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 17 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…This capacity to spread increases the possibilities of the oriental shrimp becoming an invasive species, and thus a potential problem for native carideans populations. It is possible that P. macrodactylus could compete successfully with these indigenous species for food and habitat, as Ashelby et al (2004) suggested. Like many Mediterranean carideans, P. macrodactylus is largely carnivorous (Siegfried, 1982), such as Gnathophyllum elegans, Palaemon spp., Periclimenes spp., Pontophilus spinosus, Crangon crangon and Philocheras spp.…”
Section: Discussionmentioning
confidence: 94%
“…This capacity to spread increases the possibilities of the oriental shrimp becoming an invasive species, and thus a potential problem for native carideans populations. It is possible that P. macrodactylus could compete successfully with these indigenous species for food and habitat, as Ashelby et al (2004) suggested. Like many Mediterranean carideans, P. macrodactylus is largely carnivorous (Siegfried, 1982), such as Gnathophyllum elegans, Palaemon spp., Periclimenes spp., Pontophilus spinosus, Crangon crangon and Philocheras spp.…”
Section: Discussionmentioning
confidence: 94%
“…In European waters (including Turkey), six species of Palaemon (viz. P. adspersus Rathke, 1837, P. elegans Rathke, 1837, P. longirostris H. Milne-Edwards, 1837, P. serratus (Pennant, 1777), P. xiphias Risso, 1816, and the recently introduced P. macrodactylus Rathbun, 1902(Ashelby et al, 2004Cuesta et al, 2004)) and four species of Palaemonetes (viz. P. antennarius (H. Milne-Edwards, 1837), P.…”
Section: Introductionmentioning
confidence: 99%
“…Though many studies have reported the presence of P. macrodactylus in different habitats around the world, the available information regarding life history and population traits is scarce and fragmentary ( Table 2). The presence of this species in areas with salinities that may reach values typical of marine waters has been mentioned, but no details of their life history and population dynamics have been provided (Ashelby et al 2004, Lavesque et al 2010. Consequently, this is the first comparison of population dynamics and life history traits of P. macrodactylus between a population in a fully marine area (Mar del Plata harbour) and estuarine populations.…”
Section: Discussionmentioning
confidence: 99%
“…In the southwestern Atlantic, the species was found on March 2000 in Mar del Plata harbour, Argentina, probably introduced from the Pacific with discharged ballast water (Spivak et al 2006). The recent introduction in European waters also occurred through harbours (Ashelby et al 2004, Cuesta et al 2004'Udekem d 'Acoz et al 2005, González-Ortegón et al 2007, Béguer et al 2007, Lavesque et al 2010, Chicharo et al 2009, Micu y Niţă 2009, St.Raykov et al 2010, Soors et al 2010. The distribution of the species in Asia, Europe and North America seems to be associated with estuarine or brackish water coastal areas, benefitting from the strong osmoregulatory capacity shown by adults (Born 1968 The available information on P. macrodactylus deals with the geographic distribution (above references), ecological interactions , González-Ortegón et al 2009), larval development (Little 1969), egg structure and infection (Fisher 1983a, Fisher 1983b, Fisher and Clark 1983, and morphological abnormalities (Béguer et al 2008(Béguer et al , 2010b.…”
Section: Introductionmentioning
confidence: 99%